Rapporto tra struttura e funzione della cistatina B e dei suoi mutanti in relazione all'epilessia mioclonica progressiva di tipo 1 (EPM1) - Rispoli, Ada <1982> (Alma Mater Studiorum - Università di Bologna, 2010)
This work shows for the first time that native CSTB polymerizes on addition of Cu2+ and DnaK (Hsp70). Cysteines are involved in the polymerization process and in particular at least one cysteine is necessary. We propose that Cu2+ interacts with the thiol group of cysteine and oxidize it. The oxidized cysteine modifies the CSTB structure allowing interaction with DnaK/Hsp70 to occur. Thus, Cu2+ binding to CSTB exposes a site for DnaK and such interaction allows the polymerization of CSTB. The polymers generated from native CSTB monomers, are DTT sensitive and they may represent physiological polymers. Denatured CSTB does not require Cu2+ and polymerizes simply on addition of DnaK. The polymers generated from denatured CSTB do not respond to DTT. They have characteristics similar to those of the CSTB toxic aggregates described in vivo in eukaryotic cells following CSTB over-expression. Interaction between CSTB and Hsp70 is shown by IP experiments. The interaction occurs with WT CSTB and not with the ïcys mutant. This suggests that disulphur bonds are involved. Methal-cathalyzed oxidation of proteins involves reduction of the metal ion(s) bound to the protein itself and oxidation of neighboring ammino acid residues resulting in structural modification and de-stabilization of the molecule. In this work we propose that the cysteine thyol residue of CSTB in the presence of Cu2+ is oxidized, and cathalyzes the formation of disulphide bonds with Hsp70, that, once bound to CSTB, mediates its polymerization. In vivo this molecular mechanism of CSTB polymerization could be regulated by redox environment through the cysteine residue. This may imply that CSTB physiological polymers have a specific cellular function, different from that of the protease inhibitor known for the CSTB monomer. This hypothesis is interesting in relation to Progressive Myoclonus Epilepsy of type 1 (EPM1). This pathology is usually caused by mutations in the CSTB gene. CSTB is a ubiquitous protein, but EPM1 patients have problems only in the central nervous system. Maybe physiological CSTB polymers have a specific function altered in people affected by EPM1.